Editorial. Do you want to join the meeting? - Rodriguez_Piñero Royo, Miguel; Álvarez Cortés, Juan Carlos; Calvo Gallego, Francisco Javier; Morales Ortega, José Manuel (Trabajo, Persona, Derecho, Mercado, 2020)
RESUMEN: ABSTRACT: